Juridical Analysis of the Implementation of Islamic Criminal Law in Aceh from the Perspective of Legal Hermeneutics - Irma Suryani (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
This study aims to determine the concept of the application of Islamic criminal law in Aceh and to analyze it using the perspective of legal hermeneutics. The research method used is a normative legal research method with statutory approaches (Statute Approach) and case approaches (Case Approach). The study shows that enforcing Islamic criminal law in Aceh is in the context of maintaining the five basic human needs, namely the maintenance of religion, soul, mind, lineage, and property. These five basic needs are necessary for humans. This is determined nothing but to maintain the existence of the five basic human needs, or in other words, the punishments are prescribed solely for the benefit of humans. The current implementation of Islamic law in Aceh is still within the corridor of the trilogy of religious harmony, namely inter-religious harmony, internal religious harmony, and inter-religious harmony with the Government. So if viewed through a hermeneutic lens, Islamic criminal law is basically to achieve harmonious and ideal societal conditions. In implementing Islamic criminal law, the role of all parties is needed, one of which plays an important role is the role of the family. The role is the primary milestone for providing education about Islamic law so as not to become a person who violates Islamic law.